Perbedaan Kinerja Konselor Tersertifikasi dan Belum Tersertifikasi Menyusun Program BK di SMP N SE-Kab Brebes Th. 2012 - Priyanto, Agus (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
This study aimed to see whether there are differences in performance between certified counselor with a counselor who has not been certified in developing guidance and counseling program. In this study population was all counselors at the Junior High School Brebes 155 people by the number of counselors. The research sample was selected using cluster random sampling technique as many as 41 people counselors not certified and 35 certified counselors are scattered in 16 Junior High School. Retrieval of data in this study using a questionnaire. The method of data analysis using different test (t-Test). The difference between the performance of the certified counselor and certified as yet unknown t = 2.35 with a significance level of 5%, N = 76 so that the value df = 74 while it was based on calculations, the t table = 1.99 (with interpolation). This means that t = 2.35> ttable = 1.99 in order to obtain a conclusion that there is a difference in performance between certified counselors and counselors not certified in developing the counseling program.